Intonation and Articulation: An Early Childhood Vocalization Method - Berthanica Yohana; Rien Safrina; Erlinda Yetti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of the vocalization method in improving intonation and articulation skills in early childhood. Vocalization as form of singing training is one form of training that is considered effective for use at all ages. This research uses a qualitative method with a case study approach. The case study was conducted at Pre-School X with two vocal teachers. The result show that the vocalization method creates a very significant effect in improving intonation and articulation skills because this method gives freedom and feels fun for early childhood. On the other hand, this method also succeeds in improving children’s focus when learning intonation and articulation because they do not have to divide their attention with foreign meanings and words. Therefore, the study successfully showed that the vocalization method is very effective in improving intonation and articulation skills in early childhood.